The Contribution of the Ijarah Imbt Financing Scheme to the Development of a Sustainable Halal Economy in East Lombok - Galih Mulya Subastyan; Supratman, Supratman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The rapid development of the halal economy in recent decades demands support from a robust and sustainable Islamic financial system. Among the financing instruments that play a crucial role in supporting the sustainability of this ecosystem are the ijarah and Ijarah Muntahiyah Bittamlik (IMBT) contracts. Both contracts offer asset-based financing solutions free from usury, thus aligning with Islamic economic values. Through a gradual leasing and ownership scheme, ijarah and IMBT facilitate access for businesses, particularly halal MSMEs, to productive assets without requiring large upfront capital. This approach not only encourages real sector growth and business efficiency but also expands the reach of Islamic financial services in the community. This article aims to examine the contribution of ijarah and IMBT to halal economic growth, evaluate the challenges of their implementation, and propose sustainable optimization strategies.